2002
DOI: 10.1007/s181-002-8361-7
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of outcome versus reputation: Empirical evidence for the First German Football Division

Abstract: This paper deals with the determinants of match attendance in the German premier football league. We analyse uncertainty measures of match outcome as well as uncertainty of championship outcome. Furthermore, we incorporate supporter clubs, reputation, performance measures and weather e¨ects as explanatory variables. Due to the limited capacity of the stadiums, observations on attendance are right censored in our sample. While other authors use the ordinary least squares estimator, which is inconsistent in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
105
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 15 publications
(25 reference statements)
11
105
0
4
Order By: Relevance
“…Bauer et al [37] use an online questionnaire (n = 1594 people) and show a positive impact of brand equity on attendance in German football in the 2003/04 season. Pawlowski and Anders [14] extend the model by Czarnitzki and Stadtmann [36] and find evidence of a positive impact of the away team's brand strength and uncertainty of the championship outcome in the 2005/06 season in the German Bundesliga.…”
Section: Financial Successmentioning
confidence: 84%
“…Bauer et al [37] use an online questionnaire (n = 1594 people) and show a positive impact of brand equity on attendance in German football in the 2003/04 season. Pawlowski and Anders [14] extend the model by Czarnitzki and Stadtmann [36] and find evidence of a positive impact of the away team's brand strength and uncertainty of the championship outcome in the 2005/06 season in the German Bundesliga.…”
Section: Financial Successmentioning
confidence: 84%
“…Team owners as well as managers, functionaries and public policy-makers cannot make correct judgements on issues of vital importance to them without having knowledge about demand. Since the initial research in the mid-1970s (DEMMERT, 1973;HART, HUTTON, & SHAROT, 1975;NOLL, 1974), many demand studies have been undertaken on stadium attendance (BIRD, 1982;CZARNITZKI & STADTMANN, 2002;DOBSON & GODDARD, 1992;PEEL & THOMAS, 1988;SIEGFRIED & EISENBERG, 1980;SIMMONS, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…1. It is interesting to notice that a recent empirical study done with data from the German first football division over two seasons (1996/97 and 1997/98), analysing football attendance, found that reputation (considering the performance of a given team over the last twenty years) is more important than outcome uncertainty (not statistically significant), using a generalized Tobit estimator to take into consideration that in over 25% of the cases the event was sold out (see Czarnitzki and Stadtmann 2002).…”
Section: Introductionmentioning
confidence: 99%